1990
DOI: 10.1088/0957-0233/1/8/023
|View full text |Cite
|
Sign up to set email alerts
|

Impacting particle temperature monitoring during plasma spray deposition

Abstract: Instrumentation for monitoring the thermal history of individual plasma sprayed particles as they impact on a substrate is described. A double-wavelength fibre optic temperature sensor is focused on a small spot on the substrate surface to record the cooling rate of particles impacting on this region. Discrimination against in-flight particles intersecting the pyrometer field of view is obtained by a second fibre optic sensor viewing the same spot at an angle and working in coincidence with the first sensor. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…It could also be due to errors in the pyrometric readings caused by the assumption that the splat was a gray body. The accuracy of the temperatures obtained by this method was ±100°C [15]. Lee et al [25] have shown a mathematical model capable of estimating the rate of heat transfer from droplets on a high temperature wall.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…It could also be due to errors in the pyrometric readings caused by the assumption that the splat was a gray body. The accuracy of the temperatures obtained by this method was ±100°C [15]. Lee et al [25] have shown a mathematical model capable of estimating the rate of heat transfer from droplets on a high temperature wall.…”
Section: Resultsmentioning
confidence: 96%
“…Higher temperatures will produce stronger signals, increasing the signal to noise ratio, and reducing the observed oscillations. It has been shown that, in general, the accuracy of temperature measurements obtained by the two-color pyrometry method is ±100°C [15]. Table 1 shows average values of the experimental temperatures at the maximum extent and the experimental cooling rate of molybdenum on non-heated glass.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations